Pemanfaatan Teknologi Informasi dalam Kegiatan Administrasi Perkantoran pada Kantor Desa Cikalong Kecamatan Cikalongwetan Kabupaten Bandung Barat - Muhammad Ihsan Taufiq; Cecep Wahyu Hoerudin; Ai Siti Farida (Ministrate: Jurnal Birokrasi dan Pemerintahan Daerah, 2022)
This study aims to determine how the use of information technology in the implementation of office administration and to find out the use of Information Technology in the implementation of office administration at the Cikalong Village office, Cikalongwetan District, West Bandung Regency. This type of research is descriptive qualitative with data collection techniques in the form of literature study, and field research using interview, observation and documentation methods. The results showed that information technology at the Cikalong Village Office was used to receive information, store information, organize information, send information, protect assets. Although there are obstacles in the form of inadequate facilities, and employees who have not been able to optimize information technology, the utilization of information technology has not been implemented properly.